Association of Cigarette Use and Complication Rates and Outcomes Following Total Ankle Arthroplasty. (October 2016) - Lampley, Alexander; Gross, Christopher E.; Green, Cynthia L.; DeOrio, James K.; Easley, Mark; Adams, Samuel; Nunley, James A.
Background: Tobacco use is a known risk factor for increased perioperative complications and having worse functional outcomes in many orthopedic procedures. To date, no study has elucidated the effect of cigarette smoking on complications or functional outcome scores after total ankle replacement (TAR). Methods: We retrospectively reviewed the records of 642 patients who had TAR between June 2007 and February 2014 with a known smoking status. These patients were separated into 3 groups based on their smoking status: 34 current smokers, 249 former smokers, and 359 nonsmokers. Outcome scores and perioperative complications, which included infection, wound complications, revision surgeries, and nonrevision surgeries were compared between the groups. Results: When comparing perioperative complications in the active smokers to the nonsmokers, we found a statistically significant increased risk of wound breakdown (hazard ratio [HR] 3.08, P = .047). Although the active smokers had an increased rate of infection (HR 2.61, P = .392), revision surgery (HR 1.75, P = .470), and nonrevision surgery (HR 1.69, P = .172), these findings were not statistically significant. With regard to outcome scores, all groups demonstrated improvement at 1- and 2-year follow-up compared with their preoperative outcome scores. However, the active smokers had less improvement in their outcome scores than the nonsmokers at 1- and 2-year follow-up. Furthermore, there was no significant difference in the outcome scores when comparing the nonsmokers to the former smokers. Conclusion: Active cigarette smokers undergoing TAR had a significantly higher risk of wound complications and worse outcome scores compared with nonsmokers and former smokers. Furthermore, tobacco cessation appeared to reverse the effects of smoking, which allowed TAR to be an effective and safe procedure for providing pain relief and improving function in former smokers as they had perioperative complication rates and outcomes similar to nonsmokers. Level of Evidence: Level III, retrospective comparative series.